Efficacy and safety of Shumian capsules in treating insomnia: A systematic review and meta-analysis. Issue 50 (17th December 2021) - Wang, Cuiying; Yang, Yuying; Ding, Xiao; Li, Jiamin; Zhou, Xue; Teng, Jing; Qi, Xianghua
Abstract: Background: It is known to all that the incidence of insomnia is becoming higher and higher with the increase of people's life stress. To some extent, it has brought about bad effects on people's life, work, study, and health, such as mental exhaustion, low work efficiency, and mood irritability. Now there are medications and non-medications methods for insomnia. As one of the treatments for insomnia, western medicine is to prolong the sleeping time and improve the anxious mood. However, taking western medicine to treat insomnia can also be accompanied by some adverse reactions at the same time, such as drug dependence, an allergic reaction, and so on. Traditional Chinese medicine therapy is based on syndrome differentiation and holistic concept. Shumian capsules (SM) are a kind of proprietary Chinese medicine for insomnia, which have the effect of relieving depression and calming the mind. But there are no studies on the efficacy and safety of SM in the treatment of insomnia. Therefore, I will provide a systematic review and meta-analysis to evaluate the efficacy and safety of SM for insomnia. Methods: All the studies searched were from PubMed, EMBASE, Web of Science, Cochrane Library, Chinese National Knowledge Infrastructure, and WanFang databases, and the studies types included in the analysis were all randomized controlled trials. All the retrieval contents were completed independently by 2 researchers, and a third reviewer would be involved when there existed any disagreement. The eligible studies were screened out according to the inclusion criteria and exclusion criteria, and some useful information was extracted and made into a feature table, including the year of the included studies, the age, and disease course of the participants in the studies and intervention methods, etc. Cochrane risk-of-bias tool was used to evaluate the quality of literature and meta-analysis was conducted by RevMan 5.4 software. Results: A total of 9 articles including 709 participants were included in the study after screening out. The primary outcomes of statistical analysis were cure rate and total effective rate, while the secondary outcomes included Pittsburgh sleep quality index score and incidence of adverse reactions. The results showed that Pittsburgh sleep quality index score of the SM group and Western medicine group were statistically significant (MD = –0.50, 95% confidence interval [CI] = [–0.78, –0.22], P = .0005). The total effective rate of the SM group was slightly higher than that of the Western medicine group, but there was no statistical significance (relative risk [RR] = 1.03, 95% CI = [0.95, 1.13], P = .43). Conclusion: This meta-analysis provides evidence for the efficacy and safety of SM in the treatment of insomnia, and provides a new idea for the clinical treatment of insomnia. But more research is needed to support further evidence.